Sigtuna Think Piece 9: Climate Change Education Research: What It Could Be and Why It Matters - Frans Lenglet (Environmental Association of Southern Africa, 2009)
The purpose of this think piece is to situate climate change education research in the context of research traditions, approaches and methods that are common to the social sciences, education being part thereof. At the same time it is meant to give elements for exploring the ways in which climate change education research may be identical to or different from them. This paper deliberates what climate change education research could be and why it matters. The paper argues that for climate change education research within the wider context of Education for Sustainable Development (ESD) to have effect, a research programme should build on the best of different research traditions, while avoiding the pitfalls associated with each of them. In this respect the paper argues for methodological innovation and expansion of existing forms of research. It also sees a research programme in this area has having potential to expand both research and climate change education paradigms and create opportunities for discussion, debate and continuous learning.